Studi Komparatif Buku Ajar “Marugoto Bahasa dan Kebudayaan Jepang A1” - Lisda Nurjaleka (Journal of Japanese Language Education and Linguistics, 2019)
This study examines teaching material on basic level especially textboo that focusing on communication in Japanese education. This study aims to compare two teaching materials that focus on communication competency. This research is a comparative qualitative study. The main data are the textbook of “Marugoto A1” and “J Bridge for Beginner Vol. 1”. These two textbooks are for students who learn L2 for a nonnative speaker. These two books were analysed from the point of view of teaching material analysis. We analysed the flow of learning contents and the composition of the textbook through teaching material analysis by Yoshioka (2016) theory. The results show that two subject textbooks used the same topic syllabus approach at the same basic level. This syllabus is a syllabus mainly suitable for learners in basic to intermediate levels. However, since both the textbook`s main purpose is on actual communication, it is possible that they use topic syllabus even at the first stage of beginner level.